الخصومة أسباجها وأعراضها وطرق معالجتها في ضوء سورتي البقرة وآل عمران - Wisam Jasim Ajmi Al-Saeedi (Universiti Sains Islam Malaysia, 2024)
This study deals with the causes, symptoms and methods of dispute in the light of the two verses of Al-Baqar-all and Al-Imi-an. It aimed to identify the dispute and the methods for settling it in accordance with prophetic and contemporary methods. The problematic ways for resolving the disputes represented in the absence of legal controls that start from the core of religion, and find the legal frame and controls for that. In addition, number of inquiries that illustrate the concept of dispute and its causes and symptoms in the two verses of Al-Baqar-ah and Al-Imr-an and a number of goals that answers this problem. The researcher used in this study the inductive and descriptive methods in order to reach the largest possible details. The study concluded that the term of the dispute in Holly Quran mentioned in numerous words such as: controversy, hypocrisy, argument, conflict and others. The results indicated by the study for the reasons of dispute: envy and arrogance and stubbornness and arrogance in the dispute of Iblees, non-compliance with the orders of Almighty Allah in Pharaoh's dispute with Moses (peace be upon II~III)t,h e dispute for adopting Mary (peace be upon her), the claim of Christians that Jesus (peace be upon him) is the son of Almighty Allah, the dispute for lifting of Jesus (peace be upon him) or crucified and kill him, and the sectarianism and tribal intolerance between the Oases and Khazraj tribes, the claim of Nimrod divinity and powerhl. The indications of dispute shown in the study are: the dismissal of Iblees from the mercy of Almighty Allah, striking with thunderbolt the people of Moses (peace be upon him), the destruction of Nimrod with his anny, the adoption of Mary by Zakaria (peace be upon them), Al- Mobahala (asking for Almighty Allah curse on liars) between the prophet (peace and prayer be upon him) and the delegation of Najran, and the statement of the fact for lifting Jesus (peace be upon him). The methods for dispute treatment were: forbidding and keeping away from arguments and quarrels between Muslims. This can be done by the obligation to follow the Jamaat (the group of Muslims) and the matter of virtue and prohibition of vice among the Muslims, the commitment for hearing and obedience to commands of the rolling masters by complying with their orders and follow them while it not contrary to the law of Almighty Allah. In case of dispute occurrence, Muslim has to resort to the law of Almighty Allah in the resolution of disputes, and moderation in taking the right and leave exaggeration. This will be done by considering Almighty laws in the dispute.